Method for reducing ash content and metal ion content of sulfone polymer and sulfone polymer prepared by same
By filtration and hydrochloric acid treatment in the production of sulfone polymers, the metal ion and ash content is reduced, and the problems of high-temperature boiling method in the prior art are solved, thereby achieving high purity and high-quality sulfone polymerization The preparation of the product is suitable for high-end application fields.
Patent Information
- Application Number
- CN202411105894.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-01-10
AI Technical Summary
The remaining metal ions and ash content in the existing sulfone polymer production process is relatively high, which affects the electrical performance and light transmittance of the product. The high-temperature boiling method consumes high energy and has a long production cycle, making it difficult to achieve high-purity and high-quality sulfone. Polymer preparation.
After the polymerization reaction is completed, filtration is performed to remove unreacted alkali metal salts and by-products, followed by addition of a specific concentration of aqueous hydrochloric acid solution to reduce the metal ion content, and the purity of the sulfone polymer is further improved by filtration and hydrochloric acid treatment.
It significantly reduces the metal ions and ash content in the sulfone polymer, shortens the production cycle, reduces energy consumption and washing water usage, improves the purity and applicable fields of the product, and is suitable for high-end fields such as medical hemodialysis, electronics and electrical.
Abstract
Description
Technical Field
[0001] The invention relates to a method for reducing the ash content and metal ion content of a sulfone polymer and a sulfone polymer prepared by the method, belonging to the technical field of improving the purity and quality of the sulfone polymer. Background Art
[0002] Sulfone polymer (including polysulfone, i.e. bisphenol A type polysulfone, polyethersulfone, polyphenylsulfone) is a kind of slightly amber transparent or translucent special engineering plastics, which has a series of excellent properties such as high temperature resistance, hydrolysis resistance, low molding shrinkage, strong impact toughness, non-toxic flame retardancy, etc. It is widely used in pipeline components, medical equipment, water treatment, mechanical electronics and other fields.
[0003] The production of sulfone polymers is mainly obtained by polymerizing diphenol monomers and dichlorodiphenyl sulfone under the catalysis of alkali metal salts. After the reaction is completed, a large amount of unreacted alkali metal salts and chloride salt by-product impurities will remain. The presence of these impurities will have a great impact on the electrical properties, light transmittance, color, etc. of the sulfone polymer. Purifying the sulfone polymer to reduce the content of residual catalysts and by-product metal ions therein is beneficial to improving the performance of the sulfone polymer product.
[0004] At present, the main post-treatment method for the industrial production of sulfone polymers is the boiling method, which is as follows: after the polymerization is completed, the polymer solution is transferred to a grinder and crushed into particles. During the crushing process, a part of the metal ions precipitate from the polymer into the water, while the metal ions remaining in the sulfone polymer particles require more than 4 high-temperature boiling treatments to purify the sulfone polymer. This purification method has the following obvious disadvantages: 1. The purification time is long, which increases the production cycle; 2. The large amount of wastewater generated by multiple boilings is difficult to recycle and the treatment cost is high; 3. The process of heating water will generate great energy consumption, resulting in increased costs.
[0005] Since the metal ion content in sulfone polymer products on the market is relatively high, which affects the application of sulfone polymers in the fields of medical devices, electronic appliances, etc., further reducing the metal ion content in sulfone polymer products to obtain high-purity, high-quality sulfone polymer products has always been a problem faced by technical personnel in this field. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] The object of the present invention is to solve the above-mentioned problems existing in the prior art and reduce the ash content and metal ion content of sulfone polymer.
[0008] Solutions for solving problems
[0009] In order to achieve the above-mentioned purpose, the inventors conducted in-depth research and found that: after the polymerization reaction is completed, filtering the polymer solution first can significantly remove unreacted alkali metal salts, reaction by-products such as chloride salts and other solid particulate impurities, and then adding a specific amount of hydrochloric acid aqueous solution of a specific concentration to the filtrate can further reduce the metal ion content remaining in the sulfone polymer and further reduce the ash content, thereby improving the quality of the sulfone polymer product.
[0010] The present invention provides a method for reducing the ash content and metal ion content of sulfone polymers, which comprises: adding aromatic diphenol monomers, dihalogenated diphenyl sulfone monomers, catalysts, and water-carrying agents into a solvent for polymerization reaction, wherein the catalyst is one or more of hydroxides, carbonates, and bicarbonates of sodium, potassium, and cesium;
[0011] After the viscosity of the reaction system reaches 800-1200 mPa·s, the polymerization reaction is stopped;
[0012] The obtained polymer solution is filtered;
[0013] Adding an aqueous hydrochloric acid solution to the filtered polymer solution, wherein the mass fraction of the aqueous hydrochloric acid solution is in the range of 36% to 38%, and the amount of the aqueous hydrochloric acid solution added is in the range of 2% to 10% by weight relative to the amount of the catalyst added;
[0014] The polymer solution treated with the aqueous hydrochloric acid solution is post-treated.
[0015] In the method of the present invention, the aromatic diphenol monomer is one or more of bisphenol A, bisphenol S, 4,4'-dihydroxybiphenyl, hydroquinone, resorcinol, catechol, and 4,4'-dihydroxydiphenyl ether.
[0016] In the method of the present invention, the dihalogenated diphenyl sulfone monomer is at least one of 4,4'-dichlorodiphenyl sulfone and 4,4'-difluorodiphenyl sulfone.
[0017] In the method of the present invention, the sulfone polymer is at least one of bisphenol A type polysulfone, polyether sulfone and polyphenyl sulfone.
[0018] In the method of the present invention, the molar ratio of the aromatic diphenol monomer to the dihalogenated diphenyl sulfone monomer is 1:1; preferably, the molar ratio of the catalyst to the aromatic diphenol monomer is 1.3:1.
[0019] The method of the present invention, wherein the solvent is at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-vinylpyrrolidone (NVP), 1,3-dimethyl-2-imidazolidinone (DMI), and sulfolane.
[0020] The method of the present invention, wherein the water-carrying agent is one or more of toluene, o-xylene, m-xylene, p-xylene and chlorobenzene.
[0021] The method of the present invention, wherein the post-treatment comprises precipitating the polymer solution in water.
[0022] The present invention also provides a sulfone polymer obtained by the process of the present invention.
[0023] Effects of the Invention
[0024] Compared with the conventional high-temperature boiling method, the method of the present invention can significantly reduce the ash content in the sulfone polymer from about 350ppm to below 50ppm, and significantly reduce the metal ion content from about 70ppm to below 4ppm, and can be reduced to only 0.6ppm at the lowest. Since the sulfone polymer obtained by the method of the present invention has high purity and extremely low metal ion content, the sulfone polymer can be applied in high-end fields such as medical hemodialysis, electronic and electrical, and food.
[0025] Compared with the traditional high-temperature boiling method, the method of the present invention can reduce the 5-6 times of high-temperature and high-pressure boiling in the traditional purification process to 2-3 times of normal temperature water washing, greatly shortening the production cycle, greatly improving production efficiency, significantly reducing energy consumption and significantly reducing the amount of washing water. The method of the present invention is simpler, the cost is significantly reduced, and it is suitable for industrial production and environmentally friendly. DETAILED DESCRIPTION
[0026] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0027] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0028] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0029] In this specification, the word "may" includes both performing a certain process and not performing a certain process.
[0030] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0031] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0032] The present invention provides a method for reducing the ash content and metal ion content of a sulfone polymer, comprising:
[0033] Adding an aromatic diphenol monomer, a dihalogenated diphenyl sulfone monomer, a catalyst, and a water-carrying agent into a solvent to carry out a polymerization reaction, wherein the catalyst is one or more of the hydroxides, carbonates, and bicarbonates of sodium, potassium, and cesium;
[0034] After the viscosity of the reaction system reaches 800-1200 mPa·s, the polymerization reaction is stopped;
[0035] The obtained polymer solution is filtered;
[0036] Adding an aqueous hydrochloric acid solution to the filtered polymer solution, wherein the mass fraction of the aqueous hydrochloric acid solution is in the range of 36 to 38%, and the amount of the aqueous hydrochloric acid solution added is in the range of 2% to 10% by weight relative to the amount of the catalyst added;
[0037] The polymer solution treated with the aqueous hydrochloric acid solution is post-treated.
[0038] Preferably, the filtration is performed under negative pressure, more preferably under negative pressure in the range of -0.05 MPa to -0.02 MPa.
[0039] When the amount of the hydrochloric acid aqueous solution added is in the range of 2% to 10% by weight relative to the amount of the catalyst added, the catalyst alkali metal salt remaining in the filtered polymer solution and the phenol salt at the end of the polymer molecular chain can be fully reacted without causing the precipitation of sulfone polymer. If it is below the lower limit, the residual catalyst alkali metal salt and the phenol salt at the end of the polymer molecular chain cannot be fully reacted. If it is above the upper limit, too much water is likely to cause the precipitation of sulfone polymer and block the pipeline. Preferably, the amount added is in the range of 5% to 10% by weight.
[0040] Preferably, the aromatic diphenol monomer is one or more of bisphenol A, bisphenol S, 4,4'-dihydroxybiphenyl, hydroquinone, resorcinol, catechol, and 4,4'-dihydroxydiphenyl ether.
[0041] Preferably, the dihalogenated diphenyl sulfone monomer is at least one of 4,4'-dichlorodiphenyl sulfone and 4,4'-difluorodiphenyl sulfone.
[0042] Preferably, the molar ratio of the aromatic diphenol monomer to the dihalogenated diphenyl sulfone monomer is 1:1; preferably, the molar ratio of the catalyst to the aromatic diphenol monomer is 1.3:1.
[0043] Preferably, the catalyst is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, cesium carbonate, sodium bicarbonate, and potassium bicarbonate.
[0044] Preferably, the solvent is at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-vinylpyrrolidone (NVP), 1,3-dimethyl-2-imidazolidinone (DMI), and sulfolane.
[0045] Preferably, the water-carrying agent is one or more of toluene, o-xylene, m-xylene, p-xylene, and chlorobenzene.
[0046] Preferably, the post-treatment comprises precipitating the polymer solution in water.
[0047] More preferably, the polysulfone precipitated in water is pulverized, washed with water, dried, and granulated.
[0048] Preferably, the polymerization reaction is carried out in the range of 160-230°C.
[0049] Preferably, the polymerization reaction is carried out for 5 to 10 hours.
[0050] Preferably, after adding the aromatic diphenol monomer, dihalogenated diphenyl sulfone monomer, catalyst, water-carrying agent and solvent, the air in the reaction kettle is replaced by vacuuming / filling with nitrogen. More preferably, the replacement frequency is 3 to 5 times.
[0051] Example
[0052] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0053] Example 1
[0054] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.477kg of bisphenol A, 0.288kg of sodium carbonate, 5kg of solvent N-methylpyrrolidone, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 180°C for polymerization reaction, and the polymerization time is 8h.
[0055] When the polymer solution reaches the target viscosity of 1200 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported into a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure generated by vacuuming (negative pressure value is -0.05 MPa) is used to filter and separate most of the by-product salt sodium chloride produced by the polymerization reaction, unreacted salt-forming agent sodium carbonate and other insoluble solid particle impurities.
[0056] Subsequently, the filtered polymer solution was transferred to a refining kettle, 0.0144 kg of a 36% hydrochloric acid aqueous solution (5% of the mass of the sodium carbonate feed) was added, and stirred evenly to allow the hydrochloric acid to react with the sodium phenolate at the end of the polymer molecular chain and sodium carbonate for 60 minutes.
[0057] The filtrate obtained by the hydrochloric acid treatment was injected into water for precipitation, and the polymer was crushed by a high-speed crusher, centrifuged to remove the solvent and water, washed with normal temperature water, centrifuged twice, and dried to obtain a polysulfone resin product.
[0058] The ash content and metal ion impurity content of polymer products are tested. The ash content test is carried out according to "GB T9345.1-2008 Determination of Plastic Ash Content", and the metal ion content is tested according to "HG T 3944-2007 Test of Metal Ion Content of Polyvinyl Chloride Resin ICP Method".
[0059] After testing, the polysulfone obtained in Example 1 had an ash content of 71 ppm and a sodium ion concentration of 2.4 ppm.
[0060] Example 2
[0061] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.477kg of bisphenol A, 0.288kg of sodium carbonate, 5kg of solvent N-methylpyrrolidone, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 180°C for polymerization reaction, and the polymerization time is 8h.
[0062] When the polymer solution reaches the target viscosity of 1200 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported to a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure generated by vacuuming (negative pressure value is -0.05 MPa) is used to filter and separate most of the by-product salt sodium chloride, salt-forming agent sodium carbonate and other insoluble solid particle impurities generated by the polymerization reaction.
[0063] Subsequently, the filtered polymer solution was transferred to a refining kettle, 0.0288 kg of a 36% hydrochloric acid aqueous solution (10% of the mass of the sodium carbonate feed) was added, and stirred evenly to allow the hydrochloric acid to react with the sodium phenolate at the end of the polymer molecular chain and sodium carbonate for 60 minutes.
[0064] The filtrate treated with hydrochloric acid obtained above was injected into water for precipitation, and the polymer was crushed by a high-speed crusher, centrifuged to remove the solvent and water, washed with normal temperature water, centrifuged twice, and dried to obtain a polysulfone resin product.
[0065] The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0066] The polysulfone obtained in Example 2 was tested to have an ash content of 50 ppm and a sodium ion concentration of 0.9 ppm.
[0067] Example 3
[0068] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.523kg of bisphenol S, 0.288kg of sodium carbonate, 5kg of solvent sulfolane, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the polymerization reactor, the polymerization reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 220°C for polymerization reaction, and the polymerization time is 6h.
[0069] When the polymer solution reaches the target viscosity of 1000 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported to a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure generated by vacuuming (negative pressure value is -0.05 MPa) is used to filter and separate most of the by-product salt sodium chloride, salt-forming agent sodium carbonate and other insoluble solid particle impurities generated by the polymerization reaction.
[0070] Subsequently, the filtered polymer solution was transferred to a refining kettle, 0.0144 kg of a 36% hydrochloric acid aqueous solution (5% of the mass of the sodium carbonate feed) was added, and stirred evenly to allow the hydrochloric acid to react with the sodium phenolate at the end of the polymer molecular chain and sodium carbonate for 60 minutes.
[0071] The filtrate treated with hydrochloric acid obtained above was injected into water for precipitation. At the same time, the polymer was crushed by a high-speed crusher, centrifuged to remove the solvent and water, washed with room temperature water and centrifuged twice, and dried to obtain a polymer product. The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0072] After testing, the ash content of the polymer product obtained in Example 3 was 65 ppm, and the sodium ion concentration was 2 ppm.
[0073] Example 4
[0074] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.523kg of bisphenol S, 0.288kg of sodium carbonate, 5kg of solvent sulfolane, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is vacuumed to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 220°C for polymerization reaction, and the polymerization time is 6h.
[0075] When the polymer solution reaches the target viscosity of 1000 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported to a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure generated by vacuuming (negative pressure value is -0.05 MPa) is used to filter and separate most of the by-product salt sodium chloride, salt-forming agent sodium carbonate and other insoluble solid particle impurities generated by the polymerization reaction.
[0076] Subsequently, the filtered polymer solution was transferred to a refining kettle, 0.0288 kg of a 36% hydrochloric acid aqueous solution (10% of the mass of the sodium carbonate feed) was added, and stirred evenly to allow the hydrochloric acid to react with the sodium phenolate at the end of the polymer molecular chain and sodium carbonate for 60 minutes.
[0077] The filtrate treated with hydrochloric acid obtained above was injected into water for precipitation. At the same time, the polymer was crushed by a high-speed crusher, centrifuged to remove the solvent and water, washed with room temperature water and centrifuged twice, and dried to obtain a polymer product. The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0078] After testing, the ash content of the polymer of Example 4 was 42 ppm, and the sodium ion concentration was 0.6 ppm.
[0079] Example 5
[0080] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.389kg of 4,4'-dihydroxybiphenyl, 0.288kg of sodium carbonate, 5kg of solvent sulfolane, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 220°C for polymerization reaction, and the polymerization time is 5h.
[0081] When the polymer solution reaches the target viscosity of 850 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported to a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure of -0.05 MPa generated by vacuuming is used to filter and separate most of the by-product salt sodium chloride, the salt-forming agent sodium carbonate and other insoluble solid particle impurities generated by the polymerization reaction.
[0082] Subsequently, the filtered polymer solution was transferred to a refining kettle, 0.0144 kg of a 36% hydrochloric acid aqueous solution (5% of the mass of the sodium carbonate feed) was added, and stirred evenly to allow the hydrochloric acid to react with the sodium phenolate at the end of the polymer molecular chain and sodium carbonate for 60 minutes.
[0083] The filtrate obtained by the hydrochloric acid treatment was injected into water for precipitation, and the polymer was crushed by a high-speed crusher, centrifuged to remove the solvent and water, washed with normal temperature water, centrifuged twice, and dried to obtain a polymer product.
[0084] The polymer product was tested for ash and metal ion impurity content in the same manner as in Example 1.
[0085] After testing, the ash content of the polymer of Example 5 was 70 ppm, and the sodium ion concentration was 2.6 ppm.
[0086] Example 6
[0087] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.389kg of 4,4'-dihydroxybiphenyl, 0.288kg of sodium carbonate, 5kg of solvent sulfolane, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 220°C for polymerization reaction, and the polymerization time is 5h.
[0088] When the polymer solution reaches the target viscosity of 850 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported to a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure of -0.05 MPa generated by vacuuming is used to filter and separate most of the by-product salt sodium chloride, the salt-forming agent sodium carbonate and other insoluble solid particle impurities generated by the polymerization reaction.
[0089] Subsequently, the filtered polymer solution was transferred to a refining kettle, 0.0288 kg of a 36% hydrochloric acid aqueous solution (10% of the mass of the sodium carbonate feed) was added, and stirred evenly to allow the hydrochloric acid to react with the sodium phenolate at the end of the polymer molecular chain and sodium carbonate for 60 minutes.
[0090] The filtrate obtained by the hydrochloric acid treatment was injected into water for precipitation, and the polymer was crushed by a high-speed crusher, centrifuged to remove the solvent and water, washed with normal temperature water, centrifuged twice, and dried to obtain a polymer product.
[0091] The polymer product was tested for ash and metal ion impurity content in the same manner as in Example 1.
[0092] After testing, the ash content of the polymer of Example 6 was 39 ppm, and the sodium ion concentration was 0.8 ppm.
[0093] Comparative Example 1
[0094] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.477kg of bisphenol A, 0.288kg of sodium carbonate, 5kg of solvent N-methylpyrrolidone, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 180°C for polymerization reaction, and the polymerization time is 8h.
[0095] When the polymer solution reaches the target viscosity of 1200mPa·s, the bottom pipeline of the kettle is opened, and the polymer solution is transferred to deionized water for polymer precipitation. At the same time, the polymer is crushed by a high-speed crusher and then centrifuged to remove the solvent and water. The polymer is then transferred to a washing kettle, and after adding about 20kg of deionized water, the washing kettle is sealed and heated to 120°C for soaking and washing for 3 hours. After the soaked and washed polymer is centrifuged to remove water, it is transferred to the washing kettle again for soaking and washing. This is repeated 5 times. The total water consumption for soaking and purification of each batch of products is about 100kg, and the total time is 15 hours. The polymer resin particles are centrifuged and dried to obtain a polymer product.
[0096] The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0097] After testing, the ash content of the polymer obtained in Comparative Example 1 was 350 ppm, and the sodium ion concentration was 68 ppm.
[0098] Comparative Example 2
[0099] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.477kg of bisphenol A, 0.288kg of sodium carbonate, 5kg of solvent N-methylpyrrolidone, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 180°C for polymerization reaction, and the polymerization time is 8h.
[0100] When the polymer solution reaches the target viscosity of 1200 mPa·s, the heating of the polymerization reactor is stopped and the condensation system is opened to start cooling. When the temperature of the polymerization reactor drops to 140°C, the polymer solution is transported to a continuous vacuum filter through a pipeline at the bottom of the reactor. The negative pressure of -0.05 MPa generated by vacuuming is used to filter and separate most of the by-product salt sodium chloride, the salt-forming agent sodium carbonate and other insoluble solid particle impurities generated by the polymerization reaction.
[0101] Subsequently, the filtered polymer solution is injected into water for precipitation, and at the same time, the polymer is crushed by a high-speed crusher, washed, centrifuged, and dried to obtain a polymer product.
[0102] The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0103] After testing, the ash content of the polymer obtained in Comparative Example 2 was 95 ppm, and the sodium ion concentration was 6.4 ppm.
[0104] Comparative Example 3
[0105] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.523kg of bisphenol S, 0.288kg of sodium carbonate, 5kg of solvent sulfolane, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 190°C for polymerization reaction, and the polymerization time is 6h.
[0106] When the polymer solution reaches the target viscosity of 1000mPa·s, the bottom pipeline of the kettle is opened, and the polymer solution is transferred to deionized water for resin precipitation. The polymer is crushed by a high-speed crusher and then transferred to a washing kettle. After adding about 20kg of deionized water, the washing kettle is sealed and heated to 120°C for soaking and washing for 3 hours. The polymer after soaking and washing is centrifuged to remove water and then transferred to the washing kettle for soaking and washing again. This is repeated 5 times. The total water consumption for soaking and purification of each batch of products is about 100kg, and the total time is 15 hours. The polymer particles are centrifuged and dried to obtain a polymer product.
[0107] The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0108] After testing, the ash content of the polymer obtained in Comparative Example 3 was 330 ppm, and the sodium ion concentration was 75 ppm.
[0109] Comparative Example 4
[0110] Add 0.6kg of 4,4'-dichlorodiphenyl sulfone, 0.389kg of 4,4'-dihydroxybiphenyl, 0.288kg of sodium carbonate, 5kg of solvent sulfolane, and 1kg of water-containing meta-xylene into a 10L polymerization reactor. After all the raw materials are put into the reactor, the reactor is evacuated to a negative pressure of -0.05MPa, and then nitrogen is immediately introduced to make the pressure in the reactor positive. After repeating the nitrogen replacement three times, the reactor is heated to 150°C for dehydration. After the water in the polymerization system is completely removed, the temperature is raised to 220°C for polymerization reaction, and the polymerization time is 5h.
[0111] When the polymer solution reaches the target viscosity of 850mPa·s, the bottom pipeline of the kettle is opened, and the polymer solution is transferred to deionized water for polymer precipitation. At the same time, the polymer is crushed by a high-speed crusher and then centrifuged to remove the solvent and water. The polymer is then transferred to a washing kettle, and about 20kg of deionized water is added to the sealed washing kettle and heated to 120°C for soaking and washing for 3 hours. The polymer after soaking and washing is centrifuged to remove water and then transferred to the washing kettle for soaking and washing again. This is repeated 5 times. The total water consumption for soaking and purification of each batch of products is about 100kg, and the total time is 15 hours. The polymer particles are centrifuged and dried to obtain a polymer product.
[0112] The ash content and metal ion impurity content of the polymer product were tested in the same manner as in Example 1.
[0113] After testing, the ash content of the polymer obtained in Comparative Example 4 was 310 ppm, and the sodium ion concentration was 75 ppm.
[0114] By comparing the results of comparative examples 1-4 with those of embodiments 1-6, it can be seen that by adopting the method provided by the present invention, i.e. filtering the polymer solution and treating the filtered polymer solution with a specific amount of a hydrochloric acid aqueous solution of a specific concentration, the ash content and metal ion content of the polymer are significantly reduced.
[0115] In addition, the method of the present invention only requires two normal temperature water washes instead of multiple high temperature water washes, which not only shortens the production cycle and improves production efficiency, but also reduces energy consumption and reduces the amount of washing water used.
[0116] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0117] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for reducing the ash and metal ion content of a sulfone polymer, comprising: Adding an aromatic diphenol monomer, a dihalogenated diphenyl sulfone monomer, a catalyst, and a water-carrying agent into a solvent to carry out a polymerization reaction, wherein the catalyst is one or more of the hydroxides, carbonates, and bicarbonates of sodium, potassium, and cesium; After the viscosity of the reaction system reaches 800-1200 mPa·s, the polymerization reaction is stopped; The obtained polymer solution is filtered; Adding an aqueous hydrochloric acid solution to the filtered polymer solution, wherein the mass fraction of the aqueous hydrochloric acid solution is in the range of 36% to 38%, and the amount of the aqueous hydrochloric acid solution added is in the range of 2% to 10% by weight relative to the amount of the catalyst added; The polymer solution treated with the aqueous hydrochloric acid solution is post-treated. 2 . The method according to claim 1 , wherein the aromatic diphenol monomer is one or more of bisphenol A, bisphenol S, 4,4′-dihydroxybiphenyl, hydroquinone, resorcinol, catechol, and 4,4′-dihydroxydiphenyl ether. 3 . 3 . The method according to claim 1 , wherein the dihalogenated diphenyl sulfone monomer is at least one of 4,4′-dichlorodiphenyl sulfone and 4,4′-difluorodiphenyl sulfone.
4. The method according to claim 1 or 2, wherein the sulfone polymer is at least one of bisphenol A type polysulfone, polyethersulfone, and polyphenylsulfone.
5. The method according to claim 1 or 2, wherein the molar ratio of the aromatic diphenol monomer to the dihalogenated diphenyl sulfone monomer is 1:1; preferably, the molar ratio of the catalyst to the aromatic diphenol monomer is 1.3:
1.
6. The method according to claim 1 or 2, wherein the solvent is at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-vinylpyrrolidone (NVP), 1,3-dimethyl-2-imidazolidinone (DMI), and sulfolane.
7. The method according to claim 1 or 2, wherein the water-carrying agent is one or more of toluene, o-xylene, m-xylene, p-xylene, and chlorobenzene.
8. The method according to claim 1 or 2, wherein the post-treatment comprises precipitating the polymer solution in water. 9 . A sulfone polymer obtained by the method according to claim 1 .